Land reform in ukraine: historiographical analysis - Barantsov, B. (Land Management, Cadastre and Land Monitoring, 2017)
Modern land reform, that continues in Ukraine since the beginning of the 90-th of ХХ century, is a logical result of the functioning of society and the state.. It’s prerequisites becames, especially full monopolization of state on ownership of land; absence of payment for land as one of the means of ensuring the rational use of lands; absence on workers motivation for intensive work on the land, etc.. These and other preconditions contributed to soil degradation, production of agricultural products with exceeding of maximum allowable concentrations of pollutants, development of diseases, undermine the gene pool of nature and man. Mentioned reasons determined the goal and objectives of modern land reform, which were originally set out in the preamble to the Resolution of the Verkhovna Rada of Ukraine from December 18, 1990 «On Land Reform» with following changes and additions, and in the implementation of the land-reformation measures gained more complete content. Conducted analysis shows that land reform in Ukraine leads to a change of ownership of land, contributes to solving problems of citizens by land plots, enactment of payment for land usecreation of conditions for the development of land market. Thus changing land relations, is formed legal and regulatory framework of land reform and land market. However, positive developments in the implementation of land reform to end of the 90-th years have not led to a radical and effective upgrade of agricultural production, recovery of investment processes in other branches of industry, improving of welfare of the population. Land reform measures didn’t receive adequate financial support. The ultimate goal - an economically-effective and environmentally safe use of land in Ukraine - has not been achieved. Further reforming of land relations contributed to the adoption in October 2001 of the Land Code of Ukraine in the new edition that created the legal principles of land reform. Since it’s adoption appeared legal framework that allows you to create land market. The Land Code of Ukraine solved question of compliance of Constitution of Ukraine, harmony between rules of the Land Code with rules of land laws and decrees of President of Ukraine. It contains rules of directly of direct action, in contrast to the general declarations. The next step in the development of land relations on the period of 2011 - 2020 years became Decree of the Cabinet of Ministers of Ukraine from 26.10.2011 y. № 1072-р «On approval of the action plan for land reform and create a transparent market of agricultural land» This plan envisages simplification of procedures for establishing of the boundaries of settlements, on amendments to some legislative acts of Ukraine concerning the abolition of free land privatization, about analyzing, systematization, organizing, organizing and bringing to a common electronic format of cadastral information; draft resolution on approval of documents regulating the administration of state land cadastre, approval of the Concept of the National Program of land use and protection, ect. One of the final stages of the land reform in agriculture should be the implementation of land market. The historical review of land reform, evaluation of its positive results and negative effects allow asserting, that in general it was carried overly inconsistently and not always scientifically substantiated. Its end result, due to the transition to a market economy, would be sharing and transfer of land to peasants to private ownership, establishment on this basis of market-oriented farms, implementation of fully functioning land market. The intermediate stages (the transfer of land to collective ownership, issuance of land certificates) only slowed reform, the numerous laws and regulations confused its essence and caused many irregularities in land relations. Keywords:history, land reform, legislation, land relations, agriculture